Management of pregnancy with diffuse cutaneous systemic sclerosis: a case report and literature review - Lingyun Yang (SAGE Publishing, 2021)
Diffuse cutaneous systemic sclerosis may occur in women of childbearing age. Pregnancies in this population are associated with a markedly increased risk of adverse obstetric and maternal outcomes even before the onset of symptoms related to sclerosis. We report a case involving the management and outcome of pregnancy in a 30-year-old woman with diffuse cutaneous systemic sclerosis. The course of her pregnancy was good and was assisted by a group consultation including obstetricians and rheumatologists. Vaginal delivery was the patient’s preferred choice because she had irregular skin tightness in her lower abdominal skin. She underwent induction of labor and combined spinal-epidural analgesia, and successfully delivered. Importantly, these pregnancies need to be planned, where possible, to allow the opportunity to counsel women and their partners in advance and to decrease any risks. These pregnancies should be considered high risk, and they require close antenatal monitoring and good supervision from an expert multidisciplinary team experienced in high-risk pregnancies. The management of delivery for patients with cutaneous systemic sclerosis is challenging, and vaginal delivery with labor analgesia is an alternative option to cesarean section.